Customary Law and Indigenous Peoples in The National Legal System - Supriyadi, Supriyadi (MLJ Merdeka Law Journal, 2024)
Customary law, as a dynamic legal system within society, is highly flexible because it is not constrained by formal procedures and can adapt to societal changes and needs. However, its weakness lies in the aspect of legal certainty due to its unwritten nature and the uncertainty regarding its commencement and cessation. In contrast, statutory regulations and agreements are formalized by authorized bodies, making the hierarchical position of customary law within statutory regulations unclear. Despite this, many countries, including Indonesia and India, recognize and respect customary law through constitutional or statutory acknowledgements, including the rights of Indigenous communities. This study focuses on the status and role of customary law and indigenous peoples within the national legal systems of Indonesia and India, as well as its function in managing societal life. The objectives are to describe and analyze the existence of customary law and indigenous peoples in both countries' legal frameworks and to examine the role of customary law in addressing societal and legal issues. The study employs a normative legal approach, utilizing statutory and conceptual analyses. The anticipated contribution of this study is twofold: theoretically, it aims to advance legal science, particularly in the development of Customary law concerning national legal systems; and practically, it seeks to provide insights for legal practitioners, judges, government officials, and communities in resolving legal matters, both within and outside the court system. Additionally, the study aims to offer valuable legal source materials for law and regulation formation based on living law. The study is expected to serve as a reference, especially for research on the position and role of Customary law in national law contexts.